Advancements in delivery systems for dietary polyphenols in enhancing radioprotection effects: challenges and opportunities - Yuxuan Lu; Kai Wang; Lin Hu (npj Science of Food)
Abstract Radiotherapy, a widely employed cancer treatment, often triggers diverse inflammatory responses such as radiation enteritis, pulmonary injury, pelvic inflammation, dermatitis, and osteitis. Dietary polyphenols have recently emerged as promising agents for mitigating radiation-induced inflammation. However, their clinical application faced challenges related to variable bioavailability, individual pharmacokinetics, optimal dosing, and limited clinical evidence. Current researches revealed the efficacy of bioactive small molecule polyphenols in addressing radiation-induced inflammation. In this review, along with a comprehensive examination of the etiology and categories of radiation-induced inflammatory conditions, the diversity of polyphenols and elucidating their anti-inflammatory mechanisms are explored. This study emphasizes the recent progresses in delivery systems for dietary polyphenols, aiming to enhance radioprotection effects. The optimized utilization of polyphenols, with a theoretical framework and reference guide, is of paramount relevance. Through diverse delivery mechanisms, the more effective and safer radioprotective strategies become achievable. This endeavor aspires to contribute to breakthroughs in the dietary polyphenols’ application, significantly enhancing human health protection during radiotherapy. These comprehensive insights presented here also support (pre)-clinical practices in navigating the complexities of utilizing dietary polyphenols for radioprotection, fostering advancements in the field and improving patient outcomes.